Evaluation of Trace Elements in Marine Biological Tissues by Graphite Furnace Atomic Absorption Spectrometry After Sample Treatment with Formic Acid - Moreira, Luana S.; Costa, Floriatan S.; Lidorio, Rita de Cássia; Toledo, Luan W. S.; Oliveira, Andrea; Gonzalez, Mario H. [UNESP]; da Silva, Erik G. P.; Amaral, Clarice D. B. (Springer Nature, 2022)
In this work, formic acid was used as an extracting solvent in a fast and accurate procedure for Cd and Pb determination in biological tissue by graphite furnace atomic absorption spectrometry (GF AAS). The procedure consists of adding formic acid to the sample, followed by heating and simple dilution before the determination of the analytes by GF AAS. The accuracy of the procedure was assessed by the analysis of lobster hepatopancreas (TORT-3) and bovine liver (NIST 1577b) certified reference materials, reaching recoveries of 95–100% (Cd) and 106–97% (Pb), respectively. The precision was assessed by the relative standard deviation (RSD%), with values equal to 4.9% and 4.4% for Cd and Pb, respectively. The limits of quantification were 0.010 (Cd) and 0.053 (Pb) µg g−1, being lower than the maximum values allowed by the main regulatory agencies. The proposed procedure was applied to samples of mollusks and different fish tissues from coastal areas in Brazil. For fish samples, concentrations ranged from 0.005 to 0.179 µg g−1 for Cd and 0.055–16.71 µg g−1 for Pb. In mollusk samples, the variation was 0.022–0.194 µg g−1 for Cd and 0.232–3.478 µg g−1 for Pb. The results obtained are below the maximum allowed limits, except for the sample of mollusk Phacoides pectinatus, which presented a Pb concentration twofold higher than ones recommended by regulatory agencies. The present study offers a promising, simple, high-frequency analytical procedure, low cost, and minimal environmental risk for the extraction of toxic elements in biological tissues. Also, providing low limits in compliance with the quantification limits of regulatory agencies.
Keywords: Alternative solvents; Formic acid; GF AAS; Sample preparation; Trace elements